Sertoli Cells Are Susceptible to ZIKV Infection in Mouse Testis - Sheng, Zi-Yang; Gao, Na; Wang, Zhao-Yang; Cui, Xiao-Yun; Zhou, De-Shan; Fan, Dong-Ying; Chen, Hui; Wang, Pei-Gang; An, Jing (Frontiers in Cellular and Infection Microbiology, 2017)
Flaviviruses including Dengue virus (DENV), Yellow fever virus (YFV), West Nile virus (WNV), and Japanese encephalitis virus (JEV) are global health problems that caused several serious diseases such as fever, hemorrhagic fever, and encephalitis in the past century. Recently, Zika virus (ZIKV) which spreads from Asia to American and causes millions of infections emerges as a new dangerous member of the genus of Flavivirus. Unlike other well-known flaviviruses, ZIKV can be transmitted sexually and infect testes in murine models. Its impacts on sperm functions, and the exact susceptible cells, however, are not entirely clear. To investigate these issues, we infected interferon α/β and γ receptors deficient AG6 mice with ZIKV and examined the outcomes of infection using an assortment of physiological, histopathological, immunological, and virological techniques. We found that infected mice displayed signs of reproductive system disorder, altered androgen levels in serum, and high viral load in semen and testes. Additionally, histopathological examinations revealed marked atrophy of seminiferous tubules and significant reduction in lumen size. Notably, these were accompanied by positive staining of ZIKV antigens on sertoli cells, detection of viral particles and vacuole changes within cytoplasm of sertoli cells. The susceptibility of sertoli cells to ZIKV was further validated in vitro study using cell lines. Importantly, the disruption of tight junctions within testis and altered sperm morphology were also observed in ZIKV infected mice. It is well-known that tight junctions formed by adjacent sertoli cells are major component of blood testis barrier, which plays important roles in maintenance of microenvironment for spermagenesis in testis. Taken together, these results demonstrate that sertoli cells are susceptible to ZIKV infection, which results in the disruption of tight junctions in testis and causes abnormal spermatogenesis in mice. These results also imply that long-term impact of ZIKV infection on human male reproductive system requires close monitoring.